Endovascular treatment of idiopathic intracranial hypertension: retrospective analysis of immediate and long-term results in 51 patients - Aguilar Pérez, Marta; Bäzner, Hansjörg (Neuroradiology, 2017)
Purpose: Idiopathic intracranial hypertension (IIH) is a disorder of increased intracranial pressure in the absence of any known causative factor. Sinus stenosis is common in these patients. Stenting of stenotic dural sinuses has gained popularity as a treatment option, since these stenoses may contribute to an obstruction of the venous return, and, thereby may contribute to IIH via an increase in venous sinus pressure. We evaluated the safety and efficacy of endovascular treatment in IIH with venous sinus stenosis. Methods: Fifty-one patients with IIH underwent stenting. Median age was 40 years. Clinical manifestation was headache in 74.5% of the patients and visual obscurations in 78.5%. Papilledema was present in 50/51 patients (98%), and lumbar puncture documented elevated CSF opening pressure in all but one patient (98%). Sinus stenoses were observed in all patients. Results: Endovascular treatment was successfully performed in all patients. There were no major complications encountered (i.e., live threatening or causing a deterioration of a patient’s condition equivalent to mRS 3-6). Improvement or resolution of papilledema was observed in 88% of the patients, and 84% reported improvement or resolution of the headache. Follow-up angiographies were performed in 48 patients at a median interval of 49 months and demonstrated in stent-stenosis or a de novo stenosis in 12 patients, eight of them needed re-treatment. Conclusion: Venous sinus stenting is a safe and effective alternative to other invasive treatments (e.g., optic nerve sheath fenestration, CSF diversion) in patients with IIH. The majority of patients have a persistent clinical benefit.
Gesehen am 25.09.2018